Of mottos and morals : simple words for complex virtues - Martin, Mike W., 1946- (Rowman and Littlefield Publishers, Incorporated, 2013)
Whether in slogans, catchphrases, adages or proverbs, we encounter mottos every day, but we rarely take time to reflect on them. In Of Mottos and Morals: Simple Words for Complex Virtues, Martin explores the possibility that mottos themselves are worthy of serious thought, examining how they contribute to moral guidance and help us grapple with complexity.